Analysis of ecotourism strategy in Alas Purwo National Park towards balanced tourism - Puji Wahono; Dewi Agustin Pratamasari; Meta Bara Berutu; Djoko Poernomo; Agustian B. Prasetya; Shaierah Gulabdin; Faerozh Madli (IOP Publishing Ltd, 2025)
This study aims to analyse the development of a balanced-tourism strategy in Alas Purwo National Park in Banyuwangi, Indonesia. Ecotourism is often used as a strategy towards balanced-tourism, although in practice the economic motive (tourism) is more dominant than the conservation motive (ecology) itself. This raises the question of whether ecotourism is the right way to achieve balanced-tourism in national parks. The research method used is qualitative, starting with field observations, in-depth interviews with managers, local government (tourism office), and visitors. Data were obtained through indepth interviews and focused discussions with relevant stakeholders. Data analysis was conducted systematically from data collection, data reduction, interpretation, and conclusion drawing, borrowing the Miles and Huberman framework. The results concluded that there is a need for institutional strengthening related to the achievement of a balanced-tourism strategy pursued through ecotourism. Maintaining ecological, economic and social balance is an important thing that can be achieved through cooperation with residents around the national park area, as well as increasing awareness of tourists who will enter the national park area.